Downregulation of Anger by Mental Contrasting With Implementation Intentions (MCII) - Schweiger Gallo, Inge; Bieleke, Maik; Alonso, Miguel A.; Gollwitzer, Peter M.; Oettingen, Gabriele (Frontiers in Psychology, 2018)
As anger can lead to aggressive behavior aiming at intentionally hurting somebody, the prevention of its destructive consequences with effective emotion regulation strategies is crucial. Two studies tested the idea that mental contrasting with implementation intentions (MCII) interventions would be effective in down-regulating anger. In Study 1, participants who adopted the self-regulation strategy of MCII showed significantly less anger-related negative affect after the anger induction than participants in a control condition, with positive affect staying unaffected. Results from a second study with a control condition plus three self-regulation conditions – a reappraisal, a MCII, and a reappraisal + MCII condition – suggest that participants using MCII were effective in down-regulating anger, irrespective of whether it was supplemented by reappraisal or not. The present research contributes to emotion regulation research by introducing MCII as an effective strategy that can be tailored to satisfy individual emotion regulation demands, such as dealing with experienced anger.